Overexpression of Nrf2 in bone marrow mesenchymal stem cells promotes B-cell acute lymphoblastic leukemia cells invasion and extramedullary organ infiltration through stimulation of the SDF-1/CXCR4 axis - Zheng, Lin; Pan, Chengyun; Ma, Dan; Shang, Qin; Hu, Tianzhen; Zhang, Tianzhuo; Kang, Qian; Hu, Xiuying; Cao, Shuyun; Wang, Li; Luo, Hong; Wang, Jishi (Frontiers in Pharmacology, 2024)
Background:Tumor microenvironment (TME) represents the key factor inducing leukemia development. As stromal cells within the leukemia microenvironment, Bone Marrow Mesenchymal Stem Cells (BM-MSCs) can trigger leukemia progression under certain conditions. As a critical transcription factor, nuclear factor erythroid related factor 2 (Nrf2) can modulate antioxidant response and antioxidant enzyme gene expression, and prevent various oxidative changes. We previously identified a novel mechanism by which Nrf2 promotes leukemia resistance, providing a potential therapeutic target for the treatment of drug-resistant/refractory leukemias.However, the role of Nrf2 in BM-MSCs from B-cell acute lymphoblastic leukemia (B-ALL) patients has not been clearly reported. The present work focused on investigating the effect of Nrf2 overexpression within MSCs on leukemia cell invasion, extramedullary infiltration and proliferation as well as its downstream pathway.Methods: Through clinical sample detection, in vitro cell experiments and in vivo animal experiments, the role of Nrf2 within MSCs within adult B-ALL cell migration and invasion and its potential molecular mechanism was explored through transcriptome sequencing analysis, RT-PCR, Western blot, cell migration, cell invasion, lentivirus transfection and other experiments. Results: Nrf2 was highly expressed in BM-MSCs from patients with B-ALL as well as in BM-MSCs co-cultured with leukemia cells. Overexpression of Nrf2 within MSCs significantly promoted leukemia cell migration, invasion and proliferation. The extramedullary organ infiltration rate in B-ALL model mice receiving the combined infusion of both cell types dramatically increased relative to that of leukemia cells alone, accompanied by the significantly shortened survival time. Mechanism study found that Nrf2 overexpression within MSCs promoted PI3K-AKT/ERK1/2 phosphorylation in the downstream pathway by activating SDF-1/CXCR4 axis, ultimately leading to extramedullary infiltration of leukemia cells.Conclusions:High Nrf2 expression with in MSCs enhances leukemia cell invasion and migration, which then accelerates infiltration in leukemic extramedullary organs. Targeting Nrf2 or inhibiting its downstream signal molecules may be the effective interventions for B-ALL patients treatment.